1989
DOI: 10.1139/x89-207
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antibiotics on elongation and callus and bud formation from embryonic tissue of Piceaglauca

Abstract: Strategies for the selection of transformed cells and the counterselection (clearing) of Agrobacterium in genetic engineering requires a balance between the selection pressures and the normal morphogenetic response of transformed tissue. In this paper, we report the effect of antibiotics used for plant transformation studies on the elongation and induction of buds from embryos and the induction of callus from seedling tissue of Piceaglauca. Carbenicillin, ampicillin (500 and 750 μg/mL), and cefotaxime (250 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…These levels of inhibition are similar to that reported for white spruce [13] and lobloUy pine [33].…”
Section: Selectionsupporting
confidence: 88%
See 1 more Smart Citation
“…These levels of inhibition are similar to that reported for white spruce [13] and lobloUy pine [33].…”
Section: Selectionsupporting
confidence: 88%
“…Transformed line 2-33 segregated from embryogenic tissue, which was not transformed. Kanamycin selection, which has been shown to affect organogenesis [13], may have had a deleterious effect on embryogenesis in this system. ence of one major Hind III band hybridizing with gusA (lane 11) shows that multiple intact copies of this gene, which was not selected for, are present.…”
Section: Polymerase Chain Reactionmentioning
confidence: 97%
“…We tested the effect of cefotaxime and found that the inhibitory effect of cefotaxime was roughly linear for concentrations up to 500 mg 1-1. These results were unanticipated because concentrations as high as 500 mg 1-1 were reported to have little effect on plant tissues (Pollock et al 1983;Ellis et al 1989;Tsang et al 1989). When we reduced the concentration of cefotaxime from 500 mg 1-1 tO 250 mg 1-1, callus growth was acceptable and growth of residual Agrobacterium was not a problem.…”
Section: Discussionmentioning
confidence: 99%
“…Although we attempted to simplify the procedure by plating the suspension cultures directly to shoot induction medium, this approach was unsuccessful. Second, antibiotics tend to inhibit callus growth less effectively than they inhibit organogenesis (Ellis et al 1989), potentially making selection more difficult. Finally, although our transgenic plants appeared normal, the introduction of somaclonal variation may be more likely using suspension cultures, and regeneration of plants from callus is not certain.…”
Section: Discussionmentioning
confidence: 99%
“…Under selection pressure, Agrobacterium cells could gain mutations that are resistant to the carbenicillin, which results in the overgrowth of Agrobacterium . Most antibiotics are generally expensive and may negatively affect plant cell differentiation (Ellis et al, 1989; Yu et al, 2001; Li and Qu, 2011). Therefore, a more reliable and cost-effective method to inhibit the overgrowth of Agrobacterium tumefaciens is highly desirable.…”
Section: Introductionmentioning
confidence: 99%